Cyclodextrin-based supramolecular polymeric nanoparticles for next generation gas separation membranes1. Issue 28 (28th July 2015) - Tan, Shereen; Fu, Qiang; Scofield, Joel. M. P.; Kim, Jinguk; Gurr, Paul A.; Ladewig, Katharina; Blencowe, Anton; Qiao, Greg. G.
<x xml:space="preserve">Abstract</x> Cyclodextrin-based supramolecular polyrotaxanes are for the first time used as soft nanoparticle additives for the selective layer of composite membranes. They exhibit outstanding gas transport characteristics at low additive percentages, due to the dynamic nature of the PDMS side chains.